The Level of Health Literacy of Seniors Living in Eastern Region of Poland. Preliminary Study - Kosicka, Bogumiła (Healthcare (Basel), 2020)
Health literacy (HL) is recognised as an important, modifiable factor in the self-management and health performance of elderly people. The aim of this preliminary study was to identify and analyse the level of health literacy among the elderly living in one of the eastern regions in Poland. The cross-sectional study was conducted among a convenience sample of 200 seniors aged 65+ after cognitive pre-screening with the use of the Montreal Cognitive Assessment (MoCA) scale. To collect data, the Polish version of the HLS-EU-Q47 was used. More than half of the elderly surveyed presented problematic levels of general HL (GEN-HL), and also problematic levels of other dimensions: health care health literacy (HC-HL), disease prevention health literacy (DP-HL), and health promotion health literacy (HP-HL). The level of seniors’ HL is dependent on the level of their education, place of living, participation in activities run by Daily Center for the Elderly, and their self-assessment of health condition (p < 0.05). These results imply the important message that there is a need to create initiatives and programs improving health literacy targeted at seniors living in rural areas, those with lower levels of education, and those with poor access to activities organised by institutions supporting seniors.